Study on the thermal resistance comparison on Al with SiO2 composites for electronics chips. (2020) - Pradhan, Raghuram; Chandrika, V.S.; Thilagavathi, G.; Muruganandam, D.; Hariprasad, K.; Adlin Paul, J.
Abstract: Aluminium and Silicon dioxide (Al & SiO2 ) combinations with different proportionality of weight basis specimens created with low thermal conductivity material such as G 641 Silicone grease. In this investigation three different combinations produced and tested the theoretical and actual thermal resistance for the heat transfer rate. This combination prepared for the utilization on the electronic microchip cooling purpose because of its need of cooling to maintain its performance and life of that particular electronic chip.